Analisis Hukum Pajak terhadap Praktik Penggelapan Pajak di Indonesia: Studi Kasus Dermawati Turnip - Sekar Ayu Kusuma Dewi; Ida Farida; Rika Nurrizkiana (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study analyzes the application of tax law to tax evasion practices in Indonesia through the case of Dermawati Turnip. The research focuses on the criminal aspects of taxation as regulated under Article 39 paragraph (1) letters d and i of Law No. 6 of 1983 on General Provisions and Tax Procedures (UU KUP) and its relation to Article 3 of Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering Crimes (UU TPPU). Using a normative juridical and descriptive analytical approach, the findings reveal that Dermawati intentionally failed to remit collected taxes and submitted falsified tax reports, causing significant losses to the state. The acts fulfilled all elements of criminal tax offenses with deliberate intent (dolus directus) and demonstrated a direct linkage between tax evasion and money laundering. Strengthening Indonesia’s tax enforcement requires institutional synergy, consistent sanction implementation, and the enhancement of public fiscal morality.